Karakter Morfologi Necrobia spp. (Coleoptera ; Cleridae) Pada Beberapa Jenis Bahan Simpanan - Ni Made Riska Dewi; Jusuf . Manueke; Caroulus S. Rante; Elisabeth R.M. Meray (COCOS, 2013)
ABSTRACTThe morphological and behavioral characters indicate the identity of the type or species of insects and closely related to the selection and determination of the type of insect food. This study aimed to see differences in morphological characters Necrobia spp. on some kinds of deposits. It is hoped this research can provide information on morphological characters Necrobia spp. on some kinds of deposits. This study uses survey methods, and sampling was done by "purposive sampling" is intentionally sampling by selecting and determining the sampling site. The results showed that the morphological Necrobia spp. imago on copra, dried shrimp and fish rowa there is a difference. Morphological differences Necrobia spp. imago views of body size, body color, male and female differences. Dense population Necrobia spp. imago the highest in the kopra 33.25 individu/500gr, dried shrimp followed the 31.5 individu/500 gr, then the fish rowa 27.25 individu/500gr while the peanuts are not found Necrobia spp.